An Analysis of the Dynamic Linkages of Pakistani Stock Market with the World’s Leading Stock Markets - Sajad Ahmad; Naimat U. Khan; Mumtaz Hussain Shah; Muhammad Niaz Khan (Journal of Management Practices, Humanities and Social Sciences, 2022)
Using the theoretical framework of International Portfolio Diversification (IPD), the study explores the long-run relationship between the Pakistan Stock Exchange (PSX) and the world's six leading stock exchanges of Canada, China, France, Japan, United Kingdom, and the United States. These markets are represented by the indices such as KSE-100 index (Pakistan), TSX (Canada), SSE Composite (China), CAC-40 Index (France), Nikkie-225 (Japan), FTSE-100 index (UK) and DJIA (US). An extended sample period of 27 years, has been studied ranging from 1991 to 2018, using daily, weekly, and monthly frequencies. This paper investigates the existence of cointegration among the markets by employing Johansen and Juselius bi-variate and multivariate co-integration techniques. The Augmented Dicky Fuller (ADF) and Phillip and Perron (P-P) test indicate that all the series are non stationary at level, whereas they are stationary at the first difference form. In addition, the results of the bi-variate co-integration test show that Pakistani market is weakly linked with the rest of the six markets. In addition, the findings of the multivariate co-integration test confirm two co-integrating equations—France and the UK stock exchanges are integrated on the daily data, while China and Canada stock exchanges are integrated on monthly data. An essential implication deduced from this result is that these markets are loosely connected with each other over the period investigated. Hence, international investors seeking to reduce risk can diversify their portfolio risk by including these markets in their pool of investment.